Emerging discoveries on the role of TRIM14: from diseases to immune regulation - Xinhao Li; Feilong Zhou; Kaiyi Niu; Yizhu Wang; Yanlong Shi; Yunxin Li; Xin Gao; Weijie Zhao; Tianyi Chen; Yewei Zhang (Cell Death Discovery)
Abstract TRIM14 is an important member of the TRIM family and is widely expressed in a variety of tissues. Like other members of the TRIM family, TRIM14 is also involved in ubiquitination modifications. TRIM14 was initially reported as an interferon-stimulated gene (ISG). In recent years, many studies have focused on the regulatory role of TRIM14 in signaling pathways such as the PI3K/Akt, NF-κB, and cGAS/STING pathways and revealed its mechanism of action in a variety of pathophysiological processes, and the regulation of TRIM14 has attracted the interest of many researchers as a new direction for the treatment of various diseases. However, there are no reviews on the role of TRIM14 in diseases. In this paper, we will describe the structure of TRIM14, review its role in cancer, cardiovascular disease, cervical spondylosis, inflammation and antiviral immunity, and provide an outlook on future research directions.